GCAN partner workshop: Report on lessons and recommendations for policy engagement and capacity strengthening - Magalhaes, Marilia; Bryan, Elizabeth; Go, Ara (International Food Policy Research Institute, 2025)
The Gender, Climate Change and Nutrition Integration Initiative (GCAN), led by the International Food Policy Research Institute (IFPRI), has been working to integrate gender, climate resilience, and nutrition considerations into policy, interventions, and research since 2016. Since 2023, the initiative has been working in five focal countries with support from the Gates Foundation.